Analisis Laporan Keuangan Syariah pada PT Bank Syariah Indonesia Tbk Periode 31 Maret 2025 (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Sharia financial reports are an integral part of the financial reporting system that is in accordance with the principles of Islamic law (sharia), which emphasizes fairness, transparency, and accountability. This report not only functions as a financial information tool for stakeholders, but also as a form of entity accountability in managing funds ethically and in accordance with sharia. This study aims to examine the structure, principles, and implementation of sharia financial reports, with a focus on the application of the Statement of Sharia Financial Accounting Standards (PSAK Syariah) issued by the Financial Accounting Standards Board (DSAK) of the Indonesian Institute of Accountants. The method used in this study is a qualitative descriptive approach through a literature study of regulations, scientific journals, and reporting practices at sharia financial institutions in Indonesia. The results of the study indicate that sharia financial reports have several specific elements that distinguish them from conventional financial reports, such as disclosure of profit sharing, sharia contracts (murabahah, ijarah, mudharabah, musyarakah), management of social funds (zakat, infak, sedekah, and waqf), and charity funds. The application of sharia principles in financial reports also reflects the institution's commitment to broader moral and social values, such as honesty, social responsibility, and avoidance of usury. Although adequate standards have been established, challenges in reporting practices are still found, especially in terms of technical understanding, human resource training, and the integration of a comprehensive sharia-compliant reporting system. This study contributes to the Islamic accounting literature by broadening the understanding of the importance of developing financial statements that not only meet technical aspects, but also spiritual and social values. The implications of this study are expected to encourage the improvement of the quality of Islamic financial statements and strengthen public trust in the Islamic financial system as an ethical and sustainable alternative. Keywords: Financial Statements, Sharia, PSAK, Islamic Accounting.